2016
DOI: 10.1038/nrneph.2016.9
|View full text |Cite
|
Sign up to set email alerts
|

Memory T cells in organ transplantation: progress and challenges

Abstract: Antigen-experienced T cells, also known as memory T cells, are functionally and phenotypically distinct from naive T cells. Their enhanced expression of adhesion molecules and reduced requirement for co-stimulation enables them to mount potent and rapid recall responses to subsequent antigen encounters. Memory T cells generated in response to prior antigen exposures can cross-react with other nonidentical, but similar, antigens. This heterologous cross-reactivity not only enhances protective immune responses, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 117 publications
0
50
1
Order By: Relevance
“…However, widespread application of belatacept in the clinic has been hesitant due to increased rates of aggressive early acute rejection (5). The etiology of CoB resistant rejection (CoBRR) is attributed at least in part to memory T cells, which during their development and expansion downregulate CD28 and are thereby indifferent to CD28:B7 blockade (6, 7). In addition, T effector memory (T EM ) cells possess an increased potential to proliferate and mediate immune effector functions such as leukocyte adhesion and diapedesis; teleological attributes which are invariably deleterious to the allograft (6, 8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, widespread application of belatacept in the clinic has been hesitant due to increased rates of aggressive early acute rejection (5). The etiology of CoB resistant rejection (CoBRR) is attributed at least in part to memory T cells, which during their development and expansion downregulate CD28 and are thereby indifferent to CD28:B7 blockade (6, 7). In addition, T effector memory (T EM ) cells possess an increased potential to proliferate and mediate immune effector functions such as leukocyte adhesion and diapedesis; teleological attributes which are invariably deleterious to the allograft (6, 8).…”
Section: Introductionmentioning
confidence: 99%
“…The etiology of CoB resistant rejection (CoBRR) is attributed at least in part to memory T cells, which during their development and expansion downregulate CD28 and are thereby indifferent to CD28:B7 blockade (6, 7). In addition, T effector memory (T EM ) cells possess an increased potential to proliferate and mediate immune effector functions such as leukocyte adhesion and diapedesis; teleological attributes which are invariably deleterious to the allograft (6, 8). The favorable side effect profile of belatacept has given impetus to better understanding memory T cells and development of adjuvant therapies for use with belatacept.…”
Section: Introductionmentioning
confidence: 99%
“…Blocking costimulatory signals provided by CD80 and CD86 is an effective strategy to prevent the activation of naive alloreactive T cells. 36 Taken together, these results suggest that CD28 + T EMRA cells may undergo further differentiation to lose expression of CD28 and become highly proliferative effector memory cells within the tissue and respond to alloantigen. 31 In fact, there are memory subsets in humans that completely lack the activating receptor CD28, rendering CD28 blockade therapeutics irrelevant on these memory subsets.…”
Section: Quantity Mattersmentioning
confidence: 72%
“…Likewise, in vitro stimulation of human CD28 + T EM led to rapid downregulation of CD28 such that they became CD28 null effector cells. 36 Taken together, these results suggest that CD28 + T EMRA cells may undergo further differentiation to lose expression of CD28 and become highly proliferative effector memory cells within the tissue and respond to alloantigen. These data corroborate clinical trial observations regarding T EMRA cells, CD28 expression, and acute rejection.…”
Section: Reduced Requirement For Cd28 Costimulatory Signalsmentioning
confidence: 72%
“…Indeed, antagonists of T cell adhesion in sensitized recipients improved graft survival when used in conjunction with costimulation blockade although at the considerable cost of reduced protective immunity [19]. Moreover, stable long-term tolerance to fully-mismatched allografts, even with these interventions, remained elusive [19,20]. Taking a different approach, Yamada et al [21] reported that memory T cell responses in nonhuman primates can be mitigated by a sustained effort to delete CD8 + memory T cells and delaying donor bone marrow transplantation to induce tolerance.…”
Section: Donor-specific Memory Is a Barrier To Tolerancementioning
confidence: 99%